Efeito do tratamento com o complexo paladaciclo dppe 12 associado à cisteína proteinase recombinante rldccys1 sobre a infecção por leishmania (leishmania) amazonensis em modelo murino - Silva, Danielle Aparecida Marino da [UNIFESP] (2016)
The present study evaluated the leishmanicidal activity of the cyclopalladated complex DPPE 1.2 associated to rLdccys1 in BALB/c mice infected with Leishmania (Leishmania) amazonensis. Cloning of the Ldccys1 gene encoding the cysteine proteinase 1 from L. (L.) infantum chagasi amastigotes in bacterial expression vector generated the recombinant protein rLdccys1. Cross reactivity between rLdccys1 and a cysteine proteinase of 30 kDa from L. (L.) amazonensis amastigotes was demonstrated by Western blot. The treatment of L. (L.) amazonensis-infected BALB/c mice totalizing 6.4 mg/Kg/ animal of DPPE 1.2 associated to 7.5 mg/Kg/animal of rLdccys1 resulted in a significant reduction of the lesion size compared to that from controls and in a parasite burden reduction of 25 fold in animals treated with either DPPE 1.2 alone or associated to rLdccys1. Any of the treated group displayed increase of TCD4+ and TCD8+ lymphocytes in popliteal and inguinal lymph nodes. Treatment with double concentration of DPPE 1.2 ( totalizing 13.4 mg/Kg/animal) led to a parasite burden reduction of 185 and 140 fold in animals treated with DPPE 1.2 alone and associated to rLdccys1, respectively, whereas in mice treated with rLdccys1 alone this reduction was of 4 fold compared to controls. However, results from both experiments showed that the parasite burden reduction was not statistically different among mice treated with either DPPE 1.2 alone or DPPE 1.2 associated to rLdccys1. Evaluation of active TGF-? in mouse foot lesions showed a significant reduction of this cytokine in all treated groups compared to controls. Treatment with a lower concentration of DPPE 1.2 ( totalizing 2.5 mg/Kg/animal) resulted in a significant difference of parasite burden between mice treated with DPPE 1.2 and DPPE 1.2 associated to rLdccys1 which exhibited a parasite reduction of 35 and 260 fold, respectively, while this reduction was of 5 fold in animals treated with rLdccys1 alone. In these animals the leishmanicidal activity was followed by a significant increase of T CD4+ and T CD8+ lymphocytes in popliteal and inguinal lymph nodes. In addition, there was a significant reduction of active TGF-? in foot lesions from all treated animals. On the other hand, IFN-? was not detected in foot lesion from treated groups. XIX Evaluation of serum levels of TGO, TGP and urea showed no statistically significant alterations among groups, indicating that treatment with DPPE 1.2 alone or associated to rLdccys1 did not induce hepato and nephrotoxicity. The data obtained in this work demonstrated the efficiency of the inhibitory action of DPPE 1.2 over the infection by L. (L.) amazonensis as observed previously in our laboratory and its ability to modulate the immune system of the treated animal. Treatment with palladacycle complex associated with rLdccys1 exerted leishmanicidal effect sum to the DPPE 1.2, opening perspectives to explore the potencial of this association as an alternative to chemotherapy for cutaneous leishmaniasis caused by L. (L.) amazonensis.